(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the role of the deputy dean for youth affairs in developing student leadership in higher education institutions, and the impact of their educational and organizational activities. Effective approaches are also examined through examples of projects, trainings, and social activities aimed at developing leadership skills.